Thermo-diffusion, diffusion-thermo impacts on heat and mass transfer casson fluid flow with porous medium in the presence of heat generation and radiation - Vasa Vijaya Kumar; MN. Raja Shekar; Shankar Goud Bejawada (Partial Differential Equations in Applied Mathematics)
In this study, we explore the impact that heat absorption or generation plays in time-dependent free MHD convective transport across a vertical porous plate that is subjected to thermal radiation. With the help of similarity transformation, the governing equations are converted, and the dimensionless equations that are produced as a consequence are solved numerically with the help of the finite difference approach(FDM). Figures and tables are used to illustrate and analyse in depth the impact that a variety of controlling factors have on the flow fields throughout the flow process. The numerical findings that we obtained are more in line with the study that was published. The findings show that the influence of the Casson parameter rises velocity. The velocity and concentration of the nanofluid are improved by raising the values of the Soret number factor. The velocity and temperature distributions improve as the Dufour number rises.